WP1-2 Labial gland biopsy for the investigation of neurological sjogrens. Issue 3 (14th February 2019) - Jebril, A; Lavin, T
Abstract : Objectives: Nervous System involvement in Sjogren's Syndrome (SS) commonly affects the peripheral nerves, though central nervous manifestations such as myelitis can occur. Peripheral Neuropathy has of 2%–10% of SS cohorts. 1 Involvement of different segments of the peripheral nervous system leads to a widespread spectrum of neuropathic manifestations including dorsal root gangliopathy (DRG), small fibre neuropathy (SFN), sensorimotor neuropathy (SMN), trigeminal neuropathy (TN) and vasculitic mononeuropathy (VMN). Less commonly, the central nervous system can also be affected, causing various focal or multifocal CNS disorders. In the absence of antibodies, LGB remains central to validated diagnostic criteria 2 We aimed to ascertain the yield of labial gland biopsy (LGB) for suspected Neurological Sjogrens and identify predictive factors for positive and negative biopsies. Methods: 10 year retrospective case note review of patients referred for LGB for suspected Neurological Sjogrens, from during a period of October 2007 to 2017. Demographics, Clinical syndrome, Investigations and Biopsy Results were obtained. Results: 107 patients (73.8% female, mean age 55 years) had LGB for suspected Neurological Sjögren's. Phenotypes were DRG 60/107 (56.1%), SFN 37/107 (34.6%), TM 4/107 (3.7%), TN 2/107 (1.9%), VMN 2/107 (1.9%) and SMN 1/107 (0.9%). Overall positive biopsy yield was 32/107 (29.9%). Yield in different phenotypes; DRG 11/60 (18.3%) and SFN 20/37 (54.1%). The presence or absences of SSA/SSB antibodies (p=0.35, chi) or Sicca symptoms (p=0.1, chi) were not significant in predicting a positive biopsy. Conclusions: LGB remains a vital investigation in suspected neurological Sjogrens including small fibre neuropathy. Prior investigations and different phenotype did not predict positive biopsy. Our practice and biopsy yield is similar to other published series. 3